DESIGNING AN ESP WRITING COURSE FOR PRE-INTERMEDIATE EFL ENGINEERING STUDENTS - (:unkn) unknown (UNIV NIS, FAC SCI MATH, 2019)
This paper reports the whole process on an attempt to design an ESP English Writing Course (EWC) at a pre-intermediate level for engineering students studying at English medium departments at a state university in Turkey. Designing an English Writing Course specific for engineering students is necessary since the current EWC fails to provide the students with necessary preparations for their future careers as well. Based on Hyland's (2003) guiding concepts for teaching L2 writing and following the Language Curriculum Design Model of Nation & Macalister (2010), we aim to design an EWC that will equip engineering students with specific content and terminology as well as giving them a chance to practice writing in a way that will be sufficient for their future studies at their departments and future academic and professional careers. Data were collected via face-to-face interviews with preparatory school students and instructors as well as faculty of engineering students and an instructor. Using qualitative content analysis, the needs, wants, and lacks were determined and an ESP English Writing Course Syllabus is offered as a result of this study which provides implications for developing writing skills of the mentioned group, as well as other ESP writing course contexts.
Keywords: EAP; English writing course; course development; needs analysis